Chemical space mimicry for drug discovery - Yuan, W; Jiang, D; Nambiar, D; Liew, L; Hay, M; Bloomstein, J; Lu, P; Turner, B; Le, Q; Tibshirani, R; Khatri, P; Moloney, M; et al. (American Chemical Society, 2017)
We describe a new library generation method, Machine-based Identification of Molecules Inside Characterized Space (MIMICS), that generates sets of molecules inspired by a text-based input. MIMICS-generated libraries were found to preserve distributions of properties while simultaneously increasing structural diversity. Newly identified MIMICS-generated compounds were found to be bioactive as inhibitors of specific components of the unfolded protein response (UPR) and the VEGFR2 pathway in cell-based assays, thus confirming the applicability of this methodology toward drug design applications. Wider application of MIMICS could facilitate the efficient utilization of chemical space.